Gemological Characteristics and Trace Chemical Element Analysis of Emerald in Kafubu, Zambia - Yiwei Jiang; Siyi Zhao; Zhiyi Zhang; Bo Xu (Crystals)
This study systematically analyzed the color characteristics, microscopic inclusions (including fluid and mineral inclusions), spectral properties, and chemical composition of emerald samples from Kafubu, Zambia using infrared spectroscopy, UV–visible spectroscopy, Raman spectroscopy, and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The results were then compared with research data on emeralds from Afghanistan, Brazil, China, Colombia, Ethiopia, Madagascar, Russia, and the United States. The result establishes a global classification framework for emerald origins based on chromophores (Cr, V, Fe), categorizing deposits into two distinct groups: low-Fe regions and high-Fe regions. For high-Fe type IA emeralds, particularly those from Zambia and Madagascar exhibiting exceptionally similar Fe and Mg concentrations, a multi-element discrimination approach was developed. Using microscopic infrared testing to magnify and analyze the characteristic peaks related to OD in the range of 2550–2800 cm⁻1, it can be classified as HDO-dominant, and the high alkali metal element content in Zambian emeralds can be reflected by the absence of the HDO vOD absorption peak at 2685 cm⁻1. A further in-depth analysis of the trace elements in Zambian emeralds can provide a basis for inferring the possible rich ore geology for subsequent mining and provide more effective reference data for the identification of the origin of emeralds.